Novel 7-Aryliden-3,3a,4,5,6,7-(hexahydro-5-(2-ethoxyethyl)-2-phenyl- 3-aryl-2H-pyrazolo[4,3-c]pyridine Hydrochloride: Synthesis and Structure - Zh.A. Koshetova; V.K. Yu; T.K. Iskakova; N.A. Zhumanova; K.M. Beketov; A.E. Malmakova; K.D. Praliyev; T.M. Seilkhanov; K.D. Berlin (Eurasian Chemico-Technological Journal, 2022)
A Claisen-Schmidt type reaction of 1-(2-ethoxyethyl)piperidin-4-one with different aromatic aldehydes led to corresponding dienones with a yield of 65‒71%. 7-Arylidene-3,3a,4,5,6,7-(hexahydro-5-(2-ethoxyethyl)-2-phenyl-3-aryl-2H-pyrazolo[4,3-c]pyridines were synthesized by heterocyclization of 3,5-diarylidene-piperidin-4-ones with phenylhydrazine hydrochloride in methanol at 70 °C over 4‒6 h. The X-ray crystal structure determination of 7-(p-methoxybenzyliden)-3,3a,4,5,6,7-(hexahydro-5-(2-ethoxyethyl)-2-phenyl-3-(p-methoxyphenyl)-2H-pyrazolo[4,3-c]pyridine hydrochloride (the deposition number is CCDC 862410) was completed. The piperidine and pyrazoline rings are close to a chair and envelope conformations, respectively.